Liquidez e resiliência no Direito Constitucional Brasileiro - Barros Filho, Mario Thadeu Leme de (2015)
In this thesis, we discuss the role of the Brazilian Supreme Court (STF) in the contemporary society, establishing its characteristics with the purpose of identifying the incidence of a resilient function in such body, in addition to the traditional function of keeper of the Constitution. Therefore, we brought the thoughts of Zygmunt Bauman towards a liquid modernity, showing the relevant traits of the society in which the law, that we believe to be equally liquid, is inserted. The notion of resilience, in its constitutional framework, was brought to the thesis as a particular phenomenon of this society, since we argue that the existence of constitutional resilience is only possible in the context of liquid modernity. To verify the incidence, in the Brazilian constitutional context, of this hypothesis, we firstly show the functions of constitutional courts and, then, suggest the existence of a resilient function. Finally, we look at some case studies to investigate the occurrence of resilience in the Brazilian Supreme Court, suggesting to the reader reflection regarding the performance of this Court towards the demands of our society